2020
DOI: 10.21827/jve.3.35751
|View full text |Cite
|
Sign up to set email alerts
|

When future teachers meet real learners through telecollaboration: an experiential approach to learn how to teach languages online

Abstract: The integration of technology in language teaching has been one important topic in language education and teacher training. Teacher education has been one of the aims of telecollaboration since the beginning of the 2000’s. While the first pioneers worked with small groups of students (Develotte, Mangenot, & Zourou, 2005; MüllerHartmann, 2006), more recent projects are widening the application of telecollaboration for teacher education (Baroni et al., 2019). In the present article we present an adaptation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Every effort was made to help the language learners become adjusted to this practice. Consequently, it was found that providing language learners of both contexts with more opportunities for developing cultural awareness, whilst also increasing their ability to use telecollaborative praxis, is hugely paramount, as expressed by Cappellini & Hsu (2020). Although the majority of learners of English/ Arabic as a foreign language reported that they felt they had positive perceptions after this experiment, there were still a few opposing voices regarding telecollaborative-based ICC practice.…”
Section: Discussionmentioning
confidence: 92%
“…Every effort was made to help the language learners become adjusted to this practice. Consequently, it was found that providing language learners of both contexts with more opportunities for developing cultural awareness, whilst also increasing their ability to use telecollaborative praxis, is hugely paramount, as expressed by Cappellini & Hsu (2020). Although the majority of learners of English/ Arabic as a foreign language reported that they felt they had positive perceptions after this experiment, there were still a few opposing voices regarding telecollaborative-based ICC practice.…”
Section: Discussionmentioning
confidence: 92%
“…Each year, the future teachers received instructions about the French students' Chinese language curriculum, and developed conversational activities to be carried out during their webconferencing sessions. The interested reader will find more information about the pedagogical set-up in Cappellini & Hsu (2020).…”
Section: Context and Participantsmentioning
confidence: 99%
“…As such, it is concerned with several important but understudied aspects of CALL that were identified in a recent review by Gillespie (2020), such as multimedia, online learning, and content and language integrated learning. We demonstrate this methodological approach in a case study of a telecollaboration between learners and pre-service teachers of Mandarin Chinese as a foreign language, with the latter in the role of online language tutors (Cappellini & Hsu, 2020). Our aim is to support an ecological approach by shedding new light on the perception and the use of multimodality by future teachers with the help of eye-tracking data (Stickler, Smith & Shi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For both the spring 2019 pilot and the spring 2020 exchanges, the Spanish language students in the US participated with the goal of practicing their listening and speaking skills while the graduate students in Spain participated with the goal of gaining practical teaching experience as pre-service language teachers. Other exchange models involving pre-service teacher candidates have shown that such experiences can be powerful and transformational (Cappellini & Hsu, 2020;Lenkaitis, 2020). The pre-service graduate students involved in the study were encouraged to be innovative, and session recordings revealed that many functions of the Zoom platform were utilized, including the share screen and chat features.…”
Section: Context Objectives and Project Designmentioning
confidence: 99%